2009
DOI: 10.1016/s0828-282x(09)70530-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac EASE (Ensuring Access and Speedy Evaluation) – the impact of a single-point-of-entry multidisciplinary outpatient cardiology consultation program on wait times in Canada

Abstract: Cardiac EASE reduced wait times, increased capacity and shortened time to achieve a diagnosis. The EASE model could shorten wait times for consultative services in Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 3 publications
1
39
0
Order By: Relevance
“…Single-entry models are based on queuing theory, and are well suited to services with variable wait times among consultants since patients waiting the longest can be booked into the next available appointment [10]. Although the evidence is mixed, some studies show that single-entry approaches can reduce waiting lists [10][11][12][13][14], increase the number of patients seen Page 5 [11,13,15], and improve access and efficiency of patient care with improved patient satisfaction in both surgical and outpatient settings [9][10][11]16]. Most centralized intake systems have focused on a homogenous patient population requiring a specific procedure [9][10][11]16].…”
Section: Pagementioning
confidence: 99%
“…Single-entry models are based on queuing theory, and are well suited to services with variable wait times among consultants since patients waiting the longest can be booked into the next available appointment [10]. Although the evidence is mixed, some studies show that single-entry approaches can reduce waiting lists [10][11][12][13][14], increase the number of patients seen Page 5 [11,13,15], and improve access and efficiency of patient care with improved patient satisfaction in both surgical and outpatient settings [9][10][11]16]. Most centralized intake systems have focused on a homogenous patient population requiring a specific procedure [9][10][11]16].…”
Section: Pagementioning
confidence: 99%
“…Six studies (including both simulation studies)27 30 demonstrated that SEMs increased the proportion of individuals meeting clinically recommended benchmark waiting times 2527 28 30 32 33 There was lack of consistency here also—target benchmarks were related to either WT1 or WT2 and varied depending on the procedure or jurisdiction.…”
Section: Resultsmentioning
confidence: 99%
“…Six detailed the implementation and effectiveness of SEMs,24 25 28 31–33 two simulated the outcomes of a potential implementation,27 30 two described the development of such an implementation26 28 and two assessed the views of physicians and/or patients regarding the use of SEMs 529…”
Section: Resultsmentioning
confidence: 99%
“…Electronic consultations, defined as asynchronous communications between physicians, can improve access to specialty expertise. [6][7][8] Other mechanisms, including triage to reduce low-acuity consultations, 9,10 can help improve access to quality cardiology specialty care without a face-to-face visit and are an area of active practice innovation. [11][12][13][14][15][16][17][18][19][20] In the current study, we evaluated the efficiency and safety of a triage model for outpatient CV consultation referrals from the emergency department (ED) at a large, integrated multispecialty practice.…”
mentioning
confidence: 99%